Highly efficient enrichment of intact phosphoproteins by a cadmium ion‐based co‐precipitation strategy. Issue 7 (16th February 2022) - Li, Jiangfeng; Fan, Chongyuan; Yao, Yating; Liu, Zhaochen; Li, Fangfang; Jiang, Binghua
Abstract: Selective separation and enrichment of phosphoproteins are essential for understanding their important functions in almost all cellular processes. Here, taking advantage of the feature that cadmium ion (Cd 2+ ) has an overwhelming preference for phosphates, we developed a robust and simple Cd 2+ co‐precipitation strategy for the selective isolation of intact phosphoproteins. After evaluating the feasibility of Cd 2+ in phosphoprotein precipitation, we compared the washing protocols for the removal of non‐specific binding proteins and then used the best‐performing protocol for the isolation of phosphoproteins from different complex samples. It was found that phosphoproteins can be specifically enriched from artificial protein mixtures containing α‐casein, β‐casein, and bovine serum albumin or plasma, in which bovine serum albumin or plasma were served as interferences with very high molar ratios. Applying this method to enrich phosphoproteins from complex cell lysates, a high specificity was confirmed by western blotting analysis with a phosphoprotein‐specific kit. Finally, we successfully applied this method to the purification of caseins from drinking milk, highlighting its potential application in the studies where purified phosphoproteins were required. In a word, this Cd 2+ co‐precipitation method enables universal and effective capture, enrichment, and detection of intact phosphoproteins, making it a powerful tool for the comprehensive analysis of the phosphoproteome.